2008
DOI: 10.1292/jvms.70.1111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Polymorphisms for Parentage Testing of the Jeju Horse using 20 Microsatellite Loci

Abstract: ABSTRACT. Genetic characterization of the Jeju horse (JH) was performed to construct a correct pedigree of the JH family. A total of 111 horses including 79 JH were genotyped using 20 microsatellite loci. The number of alleles varied from 5 to 11 (mean 7.45) in the JH. The observed heterozygosity and expected heterozygosity ranged from 0.293 to 0.891 and from 0.357 to 0.841, respectively. The polymorphic information contents (PIC) ranged from 0.335 to 0.816. AHT4, ASB2, ASB17, ASB23, CA425, HMS2, HMS3, HTG10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
2
12
1
Order By: Relevance
“…Although several studies [2, 8, 9, 12] reported population studies on the genetic pedigree structure of several horse breeds, only limited information is available about data needed in casework such as the power of identity and breed assignment [4, 16]. In this study, allele M and Q of ASB23 marker, G of HMS2 marker, H and L of HTG6 marker, L of HTG7 marker, E of LEX3 marker confirmed as the specific alleles unique to Halla horses.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies [2, 8, 9, 12] reported population studies on the genetic pedigree structure of several horse breeds, only limited information is available about data needed in casework such as the power of identity and breed assignment [4, 16]. In this study, allele M and Q of ASB23 marker, G of HMS2 marker, H and L of HTG6 marker, L of HTG7 marker, E of LEX3 marker confirmed as the specific alleles unique to Halla horses.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some efforts have made by breeder associations or governments to conserve native horses based on scientific ways [4,13,27]. Similarly, we started to work with the Kiso Horse Conservation Association to create a management program for conservation, and studied the genetic diversity of the Kiso horse in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A second step in this process is the collection of large-scale population data, similar to the standard operating procedure in humans and recently described for other non-human species, such as cats (Menotti-Raymond et al 2005;Coomber et al 2007), dogs (Eichmann et al 2004;Hellmann et al 2006;Kanthaswamy et al 2009;Van Asch et al 2009), cattle (Glowatzki-Mullis et al 1995Peelman et al 1998;Van de Goor et al 2011) and bison (Schnabel et al 2000). So far, only limited population data for the equine STRs are available (Choi et al 2008;Zabek & Fornal 2009).…”
Section: Introductionmentioning
confidence: 99%